Strong foundations for quality and equity in Mexican schools - Organisation for Economic Co-operation and Development (Implementing education policies, ISSN 2617-6572, 2019)
Summary.
Keywords: koulut : Meksiko; koulutus : Meksiko; koulutus : laatu : Meksiko; koulutuspolitiikka : Meksiko; koulutusjärjestelmät : Meksiko; oikeudenmukaisuus; yhdenvertaisuus